Quinolizidine alkaloids from the roots of Sophora flavescens. Issue 7 (3rd April 2022) - Li, Jian-Chun; Zhang, Zhi-Jun; Liu, Dan; Jiang, Ming-Yan; Li, Rong-Tao; Li, Hong-Mei
Abstract: Seventeen quinolizidine alkaloids, including a new matrine-type one, sophcence A (1 ), were isolated from the roots of Sophora flavescens Alt. The structure of compound 1 was elucidated by means of 1D and 2D NMR, as well as HR-ESI-MS spectroscopic data. The NMR data of (-)- Δ 7 -dehydrosophoramine (10 ) and oxy- N -methylcytisine (12 ) were reported for the first time. In addition, (+)-sophoranol (4 ) exhibited moderate inhibition on lipopolysaccharide (LPS)-induced nitric oxide (NO) production in RAW 264.7 macrophages with IC50 value of 22.14 μM, while lupanine (17 ) was found to inhibit the growth of human glioma stem cells GSC-3# at 20 μg/mL. Graphical Abstract: